Inclusive Education in Schools: Organizational-Pedagogical Aspects of the Problem - Nataliia Matveieva (Vasyl Stefanyk Precarpathian National University, 2018)
The article emphasizes that the urgent need today is to create the necessary conditions for meeting the needs of each child, regardless of its capabilities and other factors in realizing its potential, bringing benefits to society, and feeling that it is a full citizen. The author analyzes the main problems concerning the implementation of inclusive education at the present stage, examines the state of the problem's coverage in scientific works and normative-legal documents. The author focuses on a special place in the process of creating a comfortable environment for teaching children with special needs of psycho-diagnostic tools and correctional programs that need to be adapted. The article emphasizes that compliance with a number of requirements can increase the efficiency of the process of inclusive education in a comprehensive educational institution; outlines the main conditions for improving the quality of provision of educational services for children with special needs.